The Antioxidant Profiles, Lysosomal and Membrane Enzymes Activity in Patients with Acute Pancreatitis - Milnerowicz, Halina; Bukowski, Radosław; Jabłonowska, Monika; Ściskalska, Milena; Milnerowicz, Stanisław (Mediators of Inflammation, 2014)
Oxidative stress and inflammatory mediators, such as IL-6, play an important role in the pathophysiology of acute pancreatitis. The study was aimed to assess the degree of the pro/antioxidative imbalance and estimate which antioxidant plays a role in the maintenance of pro/antioxidative balance during acute pancreatitis. The study was investigated in the blood of 32 patients with acute pancreatitis and 37 healthy subjects. IL-6 concentration as early marker of inflammation was determinated. The intensity of oxidative stress was assessed by TBARS concentration. To investigate antioxidative status, the GPx and Cu/Zn SOD activities and the levels of GSH, MT, SH groups, and TRAP were measured. The concentrations of Cu and Zn as ions participating in the maintenance of antioxidant enzymes stability and playing a role in the course of disease were determinated. The activities of GGT, AAP, NAG, and β-GD as markers of tissue damage were also measured. An increase in IL-6 concentration, which correlated with Ranson criteria, and an increase in GPx activity, levels of MT, TBARS, or GGT, and NAG activities in patients group compared to healthy subjects were demonstrated. A decrease in GSH level in patients group compared to control group was noted. The studies suggest that GPx/GSH and MT play the role of the first line of defence against oxidative stress and pro/antioxidant imbalance in the course of acute pancreatitis.